Endothelial Restoration of Receptor Activity–Modifying Protein 2 Is Sufficient to Rescue Lethality, but Survivors Develop Dilated Cardiomyopathy. Issue 3 (September 2016) - Kechele, Daniel O.; Dunworth, William P.; Trincot, Claire E.; Wetzel-Strong, Sarah E.; Li, Manyu; Ma, Hong; Liu, Jiandong; Caron, Kathleen M.
Abstract : RAMPs (receptor activity–modifying proteins) serve as oligomeric modulators for numerous G-protein–coupled receptors, yet elucidating the physiological relevance of these interactions remains complex. Ramp2 null mice are embryonic lethal, with cardiovascular developmental defects similar to those observed in mice null for canonical adrenomedullin/calcitonin receptor-like receptor signaling. We aimed to genetically rescue the Ramp2 −/− lethality in order to further delineate the spatiotemporal requirements for RAMP2 function during development and thereby enable the elucidation of an expanded repertoire of RAMP2 functions with family B G-protein–coupled receptors in adult homeostasis. Endothelial-specific expression of Ramp2 under the VE-cadherin promoter resulted in the partial rescue of Ramp2 −/− mice, demonstrating that endothelial expression of Ramp2 is necessary and sufficient for survival. The surviving Ramp2 −/− Tg animals lived to adulthood and developed spontaneous hypotension and dilated cardiomyopathy, which was not observed in adult mice lacking calcitonin receptor-like receptor. Yet, the hearts of Ramp2 −/− Tg animals displayed dysregulation of family B G-protein–coupled receptors, including parathyroid hormone and glucagon receptors, as well as their downstream signaling pathways. These data suggest a functional requirement for RAMP2 in the modulation of additional G-protein–coupled receptor pathways in vivo, which is critical for sustained cardiovascular homeostasis. The cardiovascular importance of RAMP2 extends beyond the endothelium and canonical adrenomedullin/calcitonin receptor-like receptor signaling, in which future studies could elucidate novel and pharmacologically tractable pathways for treating cardiovascular diseases. Abstract : Supplemental Digital Content is available in the text.